The Value of Technological Developments Based on An Islamic Perspective - Tuti Nurhaeni; Ninda Lutfiani; Ankur Singh; Widya Febriani; Marviola Hardini (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2021)
Islamic values ​​cover all aspects of spiritual, intellectual, economic, social and scientific life. An area that has no boundaries of generations and advances in civilization such as Islam has an impact on the value of technological knowledge, messages spread through direct determination, reminders of Allah SWT blessing, proof based on the past, and allusions of science as fact through modern scientific activities. Includes 5 (five) roles of Islam in modern scientific activities, including: as a basis for scientific and technological research; implementation of epistemology; provides answers to scientific research questions, encourages exploration of nature as God's creation; as a form of value in the development of technological science. So this research is made based on an Islamic perspective related to science and technology research, which concludes that Islam provides a positive image of the value of scientific research and innovation in technological development. This research proves that the global Islamic world understands the extraordinary creations of Allah SWT which are manifested through technological science to provide individual and social welfare for human beings, and provide value to scientific technology policies from an Islamic perspective.